Rare case of multisystem sarcoidosis - Barratt, Shaney Louise (BMJ Case Rep, 2021)
Sarcoidosis is a multisystem disorder of unknown cause, characterised pathologically by granulomas and primarily affecting the lung and lymphatic system of the body. It has been termed the ‘great pretender’ due to its ability to mimic other diseases. In this article we describe a case of sarcoidosis with simultaneous rare manifestations of extrathoracic disease (thyroid, osseous and renal). It highlights the enigmatic nature of sarcoidosis and the diagnostic challenge it can pose to clinicians. A multidisciplinary approach to both diagnosis and management between endocrinology, nephrology, neurosurgical, rheumatological and respiratory teams was paramount for effective clinical improvement.